Determining consumers’ choice criteria for hospital services: a study among public, private and institutional hospitals - Tor Kadioglu, Cansu; Cavmak, Dogancan; Haque, A. K. M. Ahasanul (Türkiye Fizyoterapistler Derneği, 2021)
Purpose: Due to increasing competition in healthcare, hospitals need to be more consumer oriented. Determining the factors affecting the hospital selection of consumers and the relationship between them are beneficial for hospitals. The purpose of this study is to examine the factors affecting hospital choice of healthcare customers. Methods: The sample of 662 healthcare consumers included the study and completed the questionnaire. The data were analyzed by structural equation model. Results: The results signify that responsiveness of services and physical environment significantly and positively affects perceived medical quality. Results also indicated that the post covid perception is significantly affected by responsiveness of services and accessibility. Finally, results revealed that effects of factors differed by the type of hospitals. Conclusion: The study contributesto the understanding of patient’s expectations from and criteria on hospitals. The finding of the study is also useful for hospital managers from public, private and university hospitals to conduct an efficient marketing action.